Pengaruh Disiplin Kerja dan Kompetensi terhadap Kinerja Karyawan Pada PT. Pos Indonesia (Persero) Cabang Baturaja - Palupi Indah Sari; Darman Syafei; Nourma Wulanda (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the influence of work discipline and competence on employee performance at PT Pos Indonesia (Persero) Baturaja Branch. Data were collected through a questionnaire distributed to 30 respondents. The data analysis technique used was multiple linear regression.The partial analysis results showed that work discipline had a significant effect on employee performance, with a t-value of 4.728. Competence also significantly influenced employee performance, with a t-value of 7.048 and a significance level of 0.000, which is lower than α = 0.05. Simultaneously, work discipline and competence jointly had a significant effect on employee performance, with an F-value of 109.134. The coefficient of determination (R Square) was 0.890, indicating that 89.0% of the variation in employee performance is explained by work discipline and competence, while the remaining 11.0% is influenced by other variables not examined in this study, such as motivation, job satisfaction, stress levels, compensation systems, and job design (Nurfitriani, 2022).